Some methodological recommendations for increasing the efficiency of mastering mental arithmetic in preparatory groups - Fayzullayev Sharipboy Nurullayevich; Sevara Maxamat qizi Nazarova, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
This article discusses the use of mental arithmetic in the formation of mathematical ideas in preparatory groups. In this regard, mental arithmetic is an art and a program for educating children according to the program that develops mental perception